O‘ZBEK TILI DARSLARIDA MATNNI O‘QIB TUSHUNISHDAGI MUAMMOLAR - Sh.Saparbaeva, I. (SCIENCE and SOCIETY, 2024)
This article discusses the problems that arise in reading and understanding the text in Uzbek language classes in classes where education is conducted in foreign languages and how to overcome them.
Keywords: text; reading comprehension; assignment; types of reading; method; literary texts reading